Sytuacje trudne oraz sposoby radzenia sobie z nimi przez uczniów w szóstym i siódmym roku nauki - Misiuk , Agnieszka; Deptuła, Maria (Studia Edukacyjne, 2023)
The article brings an answer to the question of which situations students perceive as difficult and which coping strategies they rely on. The study, consisting of two surveys, was carried out in the school year 2021/2022 and was conducted in 22 classes in the sixth and seventh years. Teams were drawn from all such classes in state primary schools in one lager city. The questionnaire How Do You Cope by Zygfryd Juczyński and Nina Ogińska-Bulik was used for the diagnosis. Analysis of the results shows that girls and boys differ in their perception of difficult situations. In the girls’ group, both in the first and second survey, problems in relations with peers were indicated most frequently, and those concerning family relations were mentioned somewhat less frequently. Boys, however, most frequently indicated that difficult situations are those that concerned school. The second most frequently mentioned ones were difficulties in relationships with peers. Irrespective of the type of situation indicated by the respondents as difficult, the strategy consisting in seeking support was used least frequently and a focus on emotions was used most frequently.